Ways to optimize the labour in the communal housing complex - Buzdugan Adriana (Economy and Sociology, 2013)
The management of communal complex-residential retention can be improved through the material, spiritual service, staff, and workers in the field. The main method of efficiency of functioning of the communal system of dwelling: development tool-stimulating, determining the parameters (levers) supporting. Study of the utility function in profile all employees, workers, the use of economic-mathematical methods for solving problems, developing systems of imitation of the functioning of the overall system, studying the elasticity of exogenous origin of each parameter.